Activity-dependent downregulation of M-Type (Kv7) K+ channels surface expression requires the activation of iGluRs/Ca2+/PKC signaling pathway in hippocampal neuron. (August 2015) - Li, Cai; Lu, Qing; Huang, Pengcheng; Fu, Tianli; Li, Changjun; Guo, Lianjun; Xu, Xulin
Abstract: M-type (Kv7) K + channels, encoded by KCNQ2 – KCNQ5 genes, play a pivotal role in controlling neuronal excitability. However, precisely how neuronal activity regulates Kv7 channel translocation has not yet been fully defined. Here we reported activity-dependent changes in Kv7 channel subunits Kv7.2 and Kv7.3 surface expression by glutamate (glu). In the present study, we found that treatment with glutamate rapidly caused a specific decrease in M-current as well as Kv7 channel surface expression in primary cultured hippocampal neurons. The glutamate effects were mimicked by NMDA and AMPA. The glutamate effects on Kv7 channels were partially attenuated by pre-treatment of NMDA receptors antagonistd, l -APV or AMPA-KA receptors antagonist CNQX. The signal required Ca 2+ influx through L-type Ca 2+ channel and intracellular Ca 2+ elevations. PKC activation was involved in the glutamate-induced reduction of Kv7 channel surface expression. Moreover, a significant reduction of Kv7 channel surface expression occurred following glycine-induced "chem"-LTP in vitro and hippocampus-dependent behavioral learning training in vivo . These results demonstrated that activity-dependent reduction of Kv7 channel surface expression through activation of ionotropic glutamate receptors (iGluRs)/Ca 2+ /PKC signaling pathway might be an important molecular mechanism for regulation of neuronal excitability and synaptic plasticity. Highlights: Neuronal activity by glutamate decreases surface expression of Kv7 channels. The actions of glutamate require activation of iGluRs (NMDARs or AMPARs). The glutamate effect on Kv7 channel surface expression is Ca 2+ -dependent. Glutamate-induced reduction of Kv7 channel surface expression requires PKC activity. Activity-dependent decrease in Kv7 channel surface expression contributes to LTP.